الوعى المعلوماتى لدى طلبة الدراسات العلیا بجامعة طنطا " دراسة میدانیة " - د. نادیة سعد مرسى (المجلة الدولية لعلوم المكتبات والمعلومات)
Explore the current study of the reality of the information literacy to graduatestudents, Tanta University, so the study by subtracting the concept of informationliteracy to identify and manifestations and skills, to measure the extent ofavailability in the community of the study, to identify the most important difficultiesfacing this community in the case of the information literacy, to support thedevelopment of informatics culture among researchers and students from theMaster's degree and doctorate in particular and the academic community ingeneral